DIGITAL TOOLS AND INCLUSIVE GROWTH IN HIGHER EDUCATION: AN EMPIRICAL STUDY ALIGNED WITH SDG 4 - Singh, Akanksha; Martolia, Mukta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Purpose The purpose of this empirical study is to explore the efficacy of digital tools in enhancing learning outcomes within Indian higher education, specifically in the context of supporting Sustainable Development Goal 4 (SDG4), which aims to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all. This research seeks to identify how digital tools can facilitate improved learning experiences and outcomes, thus contributing to the broader educational objectives outlined in SDG4. The research seeks insights from a range of higher education stakeholders, including students, faculties, employers, entrepreneurs, and self-employed individuals. Study design/methodology/approach This is a study via questionnaire containing closed ended questions to gather comprehensive data from students and educators across 5 higher education institutions of Delhi/NCR. A sample of 400 educators & learners members participated in the study, providing insights into their experiences with digital learning tools. The data collected were analyzed using statistical methods to identify trends and correlations regarding the use of digital tools in the learning process. Findings The findings indicate that the integration of digital tools significantly enhances student engagement, motivation, and overall learning outcomes. Students reported increased accessibility to educational resources, institutional support, improved collaboration among peers, and a more personalized learning experience. Additionally, educators noted that digital tools facilitate more effective teaching strategies and foster an inclusive learning environment. However, challenges such as technological disparities and the need for adequate training were also identified, highlighting the importance of addressing these barriers to maximize the potential of digital tools in higher education. Originality/value This study contributes to the existing literature by providing empirical evidence on the role of digital tools in supporting SDG4 within higher education. It offers valuable insights into the benefits and challenges associated with digital learning environments, making it a significant resource for educators, policymakers, and institutions aiming to enhance educational practices through technology. The findings underscore the necessity for ongoing investment in digital infrastructure and training, ensuring that all learners and educators can benefit from the transformative potential of digital learning tools. This research not only reinforces the importance of digital education in achieving SDG4 but also serves as a call to action for stakeholders to prioritize equitable access to digital resources in higher education for inclusive growth.